The Study of Effectiveness of Ropivacaine in Axillary Brachial Plexus Block for Forearm Surgery - Acharya, Sulav; Bajracharya, GR; Gauchan, s; Dhakal, N (Nepal Medical College Journal, 2020)
Brachial plexus block is a suitable alternative to general anaesthesia for patient undergoing upper extremity surgery. Ropivacaine the S-enantiomer emerged as a possible replacement of Bupivacaine without undesirable toxic effects.Therefore this study was conducted to assess the block characteristics and side effects of 0.75% ropivacaine in axillary brachial plexus block for forearm surgeries. This interventional study was carried out in 30 patients of ASA physical status I or II, aged 18 to 60 yrs undergoing elective surgery u nder axillary brachial plexus block with 20 ml of 0.75 % Ropivacaine using ultrasound and nerve stimulator. The mean onset time of sensory block was 4.53 ± 1.18 minutes and duration of sensory block was 491.00 ± 57.45 minutes. The mean onset time of motor block was 9.17 ± 1.39 minutes and duration of motor block was 452.50 ± 52.34 minutes. The mean time for rescue analgesia or total analgesic effect was 569.47 ± 88.46 minutes. No patients developed any side effects. The result of this study concluded that Ropivacaine is a safe drug providing longer duration of sensory analgesic effect and early recovery of motor function with good operating conditions for forearm surgeries under brachial blexus block.